THE DA’WAH MOVEMENT OF USTADZ FADZLAN GARAMATAN: MUSLIM FIGURE IN ESTABLISHING ISLAMIC CIVILIZATION AT NUU WAAR (PAPUA) - Ramadoni, Muhamad Afdoli; Amin, Edi; Ratnasari, WG. Pramita; Razzaq, Abdur; Mohd Nasir, Badlihisham (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
Abstract This article explores the development and da'wah movement carried out by Ustadz Fadzlan Garamatan aimed at constructing an Islamic civilization within the Nuu Waar Papuan community. Utilizing a descriptive qualitative method with a cultural da'wah approach, the study collected primary data through observations of Ustadz Fadzlan Garamatan's da'wah activities and interviews with him in the everyday lives of the Nuu Waar people of Papua. The findings reveal that Ustadz Fadzlan, acting as a religious leader, has the ability to preach da'wah messages in the Papuan society, steering them towards productive change (taghyîr). This change stems from the people's self-awareness and desire to improve their quality of life. The civilization being built encompasses both physical welfare (material) and non-physical happiness (intellectual, mental, moral, and spiritual). Effective da'wah results in beneficial changes, ultimately leading to the creation of good ethics (akhlâq karimah). Keywords: Da'wah Movement, Islamic Civilization, Nuu Waar Abstrak Artikel ini mengkaji pengembangan dan gerakan dakwah yang dilakukan oleh Ustadz Fadzlan Garamatan dalam membangun peradaban Islam, dengan tujuan untuk mendeskripsikan dan menganalisis metode serta kegiatan dakwah pada masyarakat Nuu Waar Papua. Penelitian ini menggunakan metode kualitatif deskriptif, dengan pendekatan dakwah kultural, yang memanfaatkan data primer berupa pengamatan kegiatan dakwah Ustadz Fadzlan Garamatan pada kehidupan sehari-hari masyarakat Nuu Waar Papua. Hasil penelitian ini menunjukkan Ustadz Fadzlan berperan sebagai opinion leader memiliki kemampuan pesan dakwah di masyarakat Papua menuju perubahan (taghyîr) yang produktif. Perubahan ini muncul atas keinginan dari masyarakatnya sadar akan taraf meningkatkan kualitas kehidupan yang lebih baik. Proses peradaban yang dibangun ialah kesejahteraan fisik (materi) dan terciptanya kebahagiaan non fisik (intelektual, mental, moral, dan spiritual). Dakwah yang baik akan memberikan perubahan yang baik, sehingga puncaknya tercipta etika yang baik (akhlâq karimah). Kata Kunci: Gerakan Dakwah, Peradaban Islam, Nuu Waar